Abortion metrics: a scoping review of abortion measures and indicators. Issue 1 (29th January 2021) - Filippi, Veronique; Dennis, Mardieh; Calvert, Clara; Tunçalp, Özge; Ganatra, Bela; Kim, Caron Rahn; Ronsmans, Carine
Abstract : Consensus is lacking on the most appropriate indicators to document progress in safe abortion at programmatic and country level. We conducted a scoping review to provide an extensive summary of abortion indicators used over 10 years (2008–2018) to inform the debate on how progress in the provision and access to abortion care can be best captured. Documents were identified in PubMed and Popline and supplemented by materials identified on major non-governmental organisation websites. We screened 1999 abstracts and seven additional relevant documents. Ultimately, we extracted information on 792 indicators from 142 documents. Using a conceptual framework developed inductively, we grouped indicators into seven domains (social and policy context, abortion access and availability, abortion prevalence and incidence, abortion care, abortion outcomes, abortion impact and characteristics of women) and 40 subdomains. Indicators of access and availability and of the provision of abortion care were the most common. Indicators of outcomes were fewer and focused on physical health, with few measures of psychological well-being and no measures of quality of life or functioning. Similarly, there were few indicators attempting to measure the context, including beliefs and social attitudes at the population level. Most indicators used special studies either in facilities or at population level. The list of indicators (in online supplemental appendix) is an extensive resource for the design of monitoring and evaluation plans of abortion programmes. The large number indicators, many specific to one source only and with similar concepts measured in a multitude of ways, suggest the need for standardisation.